Low Tuberculosis (TB) Case Detection: A Health Facility-Based Study of Possible Obstacles in Kaffa Zone, Southwest District of Ethiopia - Mengistu Abayneh; Shewangizaw HaileMariam; Abyot Asres (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. In Ethiopia, the national TB case detection rate is becoming improved; still some districts are not able to meet their case detection targets which leads to ongoing spread of TB infections to family members and communities. This study was intended to assess possible obstacles contributing to low TB case detection in Kaffa zone, Southwest Ethiopia. Methods. A cross-sectional descriptive study involving qualitative and quantitative data was conducted from Mar. to Sep. 2019. Sociodemographic characteristics and data on duration of cough, whether sputum smear microscopy was requested or not, and data on TB knowledge and health care-seeking practice were collected from outpatients. Health care delivery barrier for TB case detection was also explored by using in-depth interview and FGD of health staff. Results. From 802 outpatients with coughing for 2 or more weeks of duration, 334 (41.6%) of them were not requested to have TB microscopic diagnosis. Of these, 11/324 (3.4%) of them were positive for TB after sputum smear microscopy. Only 24.2% of the outpatients were aware as they have had health education on TB disease. Twenty-eight percent of patients perceived that TB was due to exposure to cold air, and 13.5% could not mention any sign or symptom of TB. Amazingly, 54.2% of them did not have any information as current TB diagnosis and treatment is free. Thirty-five percent of the patients were taking antibiotics before visiting the health facility. The interrupted supply of TB diagnostic reagents, frequent electricity interruption, shortage of trained TB care providers, weak health information system, and weak active case finding practice were explored as the factors contributing to low TB case detection. Conclusion. Interrupted functioning of diagnostic centers, shortage of trained care providers, limited active TB case finding practice, weak health information system, and inadequate knowledge and health care-seeking practice of the patients were identified as contributors for low TB case detection. Thus, improving functioning of diagnostic centers, active TB case finding activities, and expanding health education on TB disease will help to improve TB case detection in the districts.